PENERAPAN METODE QSPM TERHADAP PEMILIHAN STRATEGI DADAR BANJOER - Garry William; Fernando Mulia (Management and Entrepreneurship Journal, 2022)
Dadar Banjoer is one of the UMKM in the culinary field that was established in 2020. However, sales from Dadar Banjoer's business tend to decrease every month. This is due to the selection of strategies that are less effective and efficient so that Dadar Banjoer's business can be said to have lost in competitive competition with its competitors. Dadar Banjoer requires an effort to choose the right alternative strategy to be applied to his business in order to be able to compete again with its competitors. This research consists of 3 stages, the first is the entry stage by compiling the Internal Factors Evaluation and External Factors Evaluation matrix. The second is the matching stage, namely the making of the Internal External Matrix and the SWOT matrix which has the aim of determining alternative strategies. The third stage is the decision stage using the Quantitative Strategic Planning Matrix using an attractiveness score to determine the best alternative strategy. In this study, researchers used a qualitative method with a descriptive approach. The purpose of this research is applied research with data collection techniques by interview and observation. Initial interviews were conducted with shop owners and employees and then identified internal factors. Then, the second interview was conducted to determine the internal and external weights and ratings, and the third interview was conducted to determine the interest score used in the QSPM method to find the best alternative strategy.